2006
DOI: 10.1097/01.pas.0000209833.69972.2b
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar Grade But Not Fuhrman Grade is Applicable to Papillary Renal Cell Carcinoma

Abstract: This study was undertaken to determine the validity of Fuhrman grading in a series of papillary renal cell carcinomas (PRCCs), to examine the interrelationship and prognostic significance of the individual components of the grading system, and further to determine whether any observed predictive value was independent of other prognostic indicators. Ninety cases of PRCC were studied. Fifty-nine tumors were of type 1 and 31 were of type 2. There were 33 TNM stage 1, 26 stage 2, 18 stage 3, and 12 stage 4 tumors,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
71
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 21 publications
1
71
1
3
Order By: Relevance
“…'s study, eighty-seven cases of chromophobe renal cell carcinoma were investigated. Authors emphasized that the fact that all the 8 dead chromophobe RCC patients had FNG-2, supports this opinion (13)(14)(15)(16)(17). According to our observations, tissue fixing is a misleading factor that complicates the evaluation.…”
Section: Discussionsupporting
confidence: 49%
“…'s study, eighty-seven cases of chromophobe renal cell carcinoma were investigated. Authors emphasized that the fact that all the 8 dead chromophobe RCC patients had FNG-2, supports this opinion (13)(14)(15)(16)(17). According to our observations, tissue fixing is a misleading factor that complicates the evaluation.…”
Section: Discussionsupporting
confidence: 49%
“…47,48 For papillary RCC it was found that of the three parameters of the Fuhrman system, neither the morphometric measures of nuclear size nor pleomorphism correlated with outcome. Nucleolar prominence, based on the microscopic high-power field showing the greatest degree of nuclear pleomorphism was significantly associated with outcome on univariate analysis, although this was not independent of pT category or TNM stage.…”
Section: Fuhrman Gradingmentioning
confidence: 95%
“…Nucleolar prominence, based on the microscopic high-power field showing the greatest degree of nuclear pleomorphism was significantly associated with outcome on univariate analysis, although this was not independent of pT category or TNM stage. 47 For chromophobe RCC not one of the three grading components was correlated with outcome, when tested separately, which raises questions as to the validity of Fuhrman grading for these tumors. 48 Importantly, when tumors in both of these series were classified on the basis of nuclear size alone, utilizing the nuclear diameter cut points proposed by Fuhrman, then all tumors were classified as grade 1, whereas assessment of focal nucleolar prominence on its own showed 58% of papillary RCC and 24% of chromophobe RCC to exhibit grade 3 characteristics.…”
Section: Fuhrman Gradingmentioning
confidence: 99%
“…Cases were subtyped into type 1 and 2 PRCC by a single expert genito-urinary pathologist (J.W.S) in accordance with Delahunt and Eble's original description (9). Because nucleolar grade but not Fuhrman grade is applicable for PRCC, all tumors were regraded according to the scheme described by Sika-Paotonu (16). Additional information included sarcomatoid features, collecting system invasion, necrosis, and multifocality.…”
mentioning
confidence: 99%